2018
DOI: 10.1590/0103-1104201811613
|View full text |Cite
|
Sign up to set email alerts
|

Ações voltadas ao controle do Diabetes Mellitus na Atenção Básica: proposta de modelo avaliativo

Abstract: RESUMO O artigo corresponde à apreciação da viabilidade para avaliação das ações voltadas ao controle do Diabetes Mellitus (DM) na Atenção Básica (AB) e apresenta uma proposta de modelo avaliativo. Análises documentais, revisão de literatura e reuniões com especialistas orientaram a elaboração do modelo. Para sua validação, utilizou-se a técnica de conferência de consenso. A matriz de análise e julgamento é composta por 19 indicadores agregados em duas dimensões. As ações voltadas ao controle do DM na AB são p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0
45

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 22 publications
0
13
0
45
Order By: Relevance
“…2019;13:e240388 https://doi.org/10.5205/1981-8963.2019.240388 the increased vulnerability, therefore, it is necessary to direct health actions to prioritize individuals who fit this category in order to achieve success in interventions. 12 However, although the Northeast region is marked by the economic characteristics mentioned, the scenario of hospitalizations and deaths presented a decreasing behavior over the years of study. It is suggested that these results may reflect a possible effectiveness of PHC in controlling the disease.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…2019;13:e240388 https://doi.org/10.5205/1981-8963.2019.240388 the increased vulnerability, therefore, it is necessary to direct health actions to prioritize individuals who fit this category in order to achieve success in interventions. 12 However, although the Northeast region is marked by the economic characteristics mentioned, the scenario of hospitalizations and deaths presented a decreasing behavior over the years of study. It is suggested that these results may reflect a possible effectiveness of PHC in controlling the disease.…”
Section: Resultsmentioning
confidence: 96%
“…It is emphasized that another point that must be taken into consideration is the insufficient living conditions of Brazilian society that contribute to the emergence of individuals or groups with greater social vulnerability, as there is a feeling of exclusion from the system and basic rights such as health, education, work and leisure, evolving to the loss of freedom of choice in view of the narrow range of opportunities. 12 It is noteworthy that the increase in morbidity and mortality due to DM is directly proportional to DISCUSSION J Nurs UFPE on line. 2019;13:e240388 https://doi.org/10.5205/1981-8963.2019.240388 the increased vulnerability, therefore, it is necessary to direct health actions to prioritize individuals who fit this category in order to achieve success in interventions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Classificação fisiopatológica do Pé diabético Atenção Básica de Saúde é a referência de assistência para portadores de diabetes, pois coordena o cuidado no sistema de saúde. O cuidado deve ser prestado de forma que abranja os princípios doutrinários do SUS para evitar intercorrências que levem o paciente à hospitalização ou óbito[14].…”
unclassified